Synthesis and Evaluation of Analgesic/Anti-Inflammatory and Antimicrobial Activities of 3-Substituted - Tozkoparan, B.; Akkol, E.; Yeşİlada, E.; Işík, Ş.; Özalp, M.; Ertan, M. (Editio Cantor Verlag GmbH, 2005)
In this study, the synthesis of a novel series of Mannich bases of 5-mercapto-3-aryl-1,2,4-triazoles is described. The structures attributed to compounds 1a-5e were elucidated using IR and 1H-NMR spectroscopic techniques besides elemental analysis. The formation of 1-aminomethyl-3- substituted-1,2,4-triazole-5-thiones - not the isomeric 3-substituted-4- aminomethyl-1,2,4-triazole-5-thiones - was unambiguously confirmed by X-ray crystallographic analysis of 1c. The compounds were examined for their in vivo anti-inflammatory and analgesic activity in two different bioassays, namely carrageenan-induced hind paw edema and p-benzoquinone-induced abdominal constriction tests in mice, respectively. In addition, the ulcerogenic effects of the compounds were determined. Among the tested derivatives most promising results were obtained for the compounds bearing a nonsubstituted phenyl group at C-3 position of the triazole ring (1a-e). The compounds were also evaluated for their in vitro antimicrobial activity against a series of gram positive bacteria [Staphylococcus aureus (ATCC 29213), Enterococcus faecalis (ATCC 29212)], gram negative bacteria [Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853)] and yeast-like microorganisms [Candida albicans (ATCC 90028), C. krusei (ATCC 6258), C. parapsilosis (ATCC 22019)]. One series of the examined compounds (3a-e) exhibited better antibacterial activity especially against gram positive bacteria than against gram negative bacteria. Compounds 2c, 3b, and 3e were found to be more effective against C. parapsilosis compared with the other derivatives (MIC: 16 μg/ mL). © ECV · Editio Cantor Verlag, Aulendorf.
Keywords: 5-Mercapto-3-Aryl-1,2,4-Triazoles, Analgesic/Anti-Inflammatory Activities, Antimicrobial Activities, Mannich Bases, Synthesis; Analgesics; Anti-Inflammatories; Antimicrobials